NADH:Cytochrome b5 Reductase and Cytochrome b5 Can Act as Sole Electron Donors to Human Cytochrome P450 1A1-Mediated Oxidation and DNA Adduct Formation by Benzo[a]pyrene - Stiborová, Marie; Indra, Radek; Moserová, Michaela; Frei, Eva; Schmeiser, Heinz H; Kopka, Klaus; Phillips, David H; Arlt, Volker M (Chemical research in toxicology, 2016)
Benzo[a]pyrene (BaP) is a human carcinogen that covalently binds to DNA after activation by cytochrome P450 (P450). Here, we investigated whether NADH:cytochrome b5 reductase (CBR) in the presence of cytochrome b5 can act as sole electron donor to human P450 1A1 during BaP oxidation and replace the canonical NADPH:cytochrome P450 reductase (POR) system. We also studied the efficiencies of the coenzymes of these reductases, NADPH as a coenzyme of POR, and NADH as a coenzyme of CBR, to mediate BaP oxidation. Two systems containing human P450 1A1 were utilized: human recombinant P450 1A1 expressed with POR, CBR, epoxide hydrolase, and cytochrome b5 in Supersomes and human recombinant P450 1A1 reconstituted with POR and/or with CBR and cytochrome b5 in liposomes. BaP-9,10-dihydrodiol, BaP-7,8-dihydrodiol, BaP-1,6-dione, BaP-3,6-dione, BaP-9-ol, BaP-3-ol, a metabolite of unknown structure, and two BaP-DNA adducts were generated by the P450 1A1-Supersomes system, both in the presence of NADPH and in the presence of NADH. The major BaP-DNA adduct detected by (32)P-postlabeling was characterized as 10-(deoxyguanosin-N(2)-yl)-7,8,9-trihydroxy-7,8,9,10-tetrahydro-BaP (assigned adduct 1), while the minor adduct is probably a guanine adduct derived from 9-hydroxy-BaP-4,5-epoxide (assigned adduct 2). BaP-3-ol as the major metabolite, BaP-9-ol, BaP-1,6-dione, BaP-3,6-dione, an unknown metabolite, and adduct 2 were observed in the system using P450 1A1 reconstituted with POR plus NADPH. When P450 1A1 was reconstituted with CBR and cytochrome b5 plus NADH, BaP-3-ol was the predominant metabolite too, and an adduct 2 was also generated. Our results demonstrate that the NADH/cytochrome b5/CBR system can act as the sole electron donor both for the first and second reduction of P450 1A1 during the oxidation of BaP in vitro. They suggest that NADH-dependent CBR can replace NADPH-dependent POR in the P450 1A1-catalyzed metabolism of BaP.
Keywords: Benzo(a)pyrene; benzopyren; oxidace-redukce; adukty DNA; Oxidation-Reduction; lidé; Humans; cytochrom-B(5)-reduktasa; DNA Adducts; Cytochrome-B(5) Reductase